221k views
2 votes
Simplify the expression: (2 x^2 y^5)(3 x^3 y^3)

A) 6 x2/3 y5/3
B) 6 x-1 y 2
C) 6 x6 y15
D) 6 x5 y8

User Lephix
by
6.0k points

2 Answers

5 votes


(2x^2y^5)(3x^3y^3)=(2)(3)(x^2x^3)(y^5y^3)\\\\=6x^(2+3)y^(5+3)=6x^5y^8\to\boxed{D).}\\\\Used:\\\\a^n\cdot a^m=a^(n+m)

User Farhan C K
by
5.1k points
2 votes

(2x²y⁵)(3x³y³)

Multiply the coefficients and add the exponents.

2 * 3 = 6

x² * x³ = x²⁺³ = x⁵

y⁵ * y³ = y⁵⁺³ = y⁸

Put it all together for you answer, 6x⁵y⁸, option D

User Citrullin
by
5.3k points